2017
DOI: 10.1111/jpn.12823
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and lipid metabolism disorders in the chickens with dexamethasone‐induced oxidative stress

Abstract: The purpose of this study was to investigate the effects of long-term treatment with dexamethasone (DEX) on the antioxidation and nutrition metabolism in broiler chickens. Broilers were placed on a high-nutrient diet for 41 days, and half were given orally DEX-supplemented water at 20 mg/L every other day from 19 to 41 days of age. DEX treatment downregulated superoxide dismutase activity as well as the mRNA expression of CuZn-superoxide dismutase and glutathione peroxidase with a decrease in GSH/GSSG ratio an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 44 publications
8
16
0
1
Order By: Relevance
“…Additionally, BWG during the recovery period, d14–d28, was similar between DexF 1 and BMD+DexF 1 , which may indicate bacteria targeted by BMD are not an influential component in either weight gain or loss in association with dietary Dex. It is more likely that effects on body weight are the result of altercations in nutrient utilization and changes in fat deposition at the expense of protein, as speculated in the literature [7,11,46,47]. The expected drop in BW and BWG was present in all three experiments, but no particular bacterial species seemed to play a role in this phenomenon after feeding dexamethasone alone or in combination with BMD or Baytril after one week.…”
Section: Discussionmentioning
confidence: 58%
“…Additionally, BWG during the recovery period, d14–d28, was similar between DexF 1 and BMD+DexF 1 , which may indicate bacteria targeted by BMD are not an influential component in either weight gain or loss in association with dietary Dex. It is more likely that effects on body weight are the result of altercations in nutrient utilization and changes in fat deposition at the expense of protein, as speculated in the literature [7,11,46,47]. The expected drop in BW and BWG was present in all three experiments, but no particular bacterial species seemed to play a role in this phenomenon after feeding dexamethasone alone or in combination with BMD or Baytril after one week.…”
Section: Discussionmentioning
confidence: 58%
“…In the present study, the serum AST and ALP levels in Groups A and B were not significantly different from the control group. It has been shown that DEX treatment may increase ALT and AST levels in serum of broilers at 3 weeks of age; however, there was no significant difference of ALT and AST values in weeks 4, 5, and 6 [ 35 ]. A similar report was found in another research [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…To better ascertain the impacts of dietary CM on broilers, the metabolomic profile of cecal digesta, as well as pancreas, liver, and breast muscle tissues, was examined. These three tissues have an important role in carbohydrate metabolism [ 11 ], digestion [ 12 ], and in the health status of birds [ 13 ], respectively; in addition, breast tissue is a high value meat outcome of broiler production. Finally, the metabolome of the cecal digesta provides a key insight into the functioning of the microbiota present in the cecum and reflects changes in community structure observed using sequencing.…”
Section: Introductionmentioning
confidence: 99%